사료 첨가제 조성물 - LUND SUSAN ARENT; WALSH MARIA; MILLAN LUIS FERNANDO ROMERO; PAYLING LAURA; KIARIE ELIJAH G (2018)
적어도 하나의 프로테아제와의 조합으로 하나 이상의 박테리아 균주를 포함하는 직접 섭취 미생물로 본질적으로 구성되는 사료 첨가제 조성물 및 대상체의 퍼포먼스 개선 방법 또는 사료에서 원료의 소화력 개선 방법으로서, 프로테아제와의 조합으로 직접 섭취 미생물을 대상체에 투여하는 단계를 포함하는 방법이 개시된다. Disclosed is feed additive composition consisting essentially of a direct fed microbial comprising one or more bacterial strains in combination with at least one protease and a method for improving the performance of a subject or for improving digestibility of a raw material in a feed, which method comprising administering to a subject a direct fed microbial in combination with a protease.